Two-polymerase mechanisms dictate error-free and error-prone translesion DNA synthesis in mammals - Shachar, Sigal (Nature Publishing Group, 2009)
DNA replication across blocking lesions occurs by translesion DNA synthesis (TLS), involving a multitude of mutagenic DNA polymerases that operate to protect the mammalian genome. Using a quantitative TLS assay, we identified three main classes of TLS in human cells: two rapid and error-free, and the third slow and error-prone. A single gene, REV3L, encoding the catalytic subunit of DNA polymerase ζ (polζ), was found to have a pivotal role in TLS, being involved in TLS across all lesions examined, except for a TT cyclobutane dimer. Genetic epistasis siRNA analysis indicated that discrete two-polymerase combinations with polζ dictate error-prone or error-free TLS across the same lesion. These results highlight the central role of polζ in both error-prone and error-free TLS in mammalian cells, and show that bypass of a single lesion may involve at least three different DNA polymerases, operating in different two-polymerase combinations.